2007
DOI: 10.1264/jsme2.22.175
|View full text |Cite
|
Sign up to set email alerts
|

Culturable Endophytic Bacterial Flora of the Maturing Leaves and Roots of Rice Plants (Oryza sativa) Cultivated in a Paddy Field

Abstract: The culturable endophytic bacteria in the leaves and roots of rice plants (Oryza sativa, cultivar Kinuhikari) cultivated on an experimental plot adjacent to a paddy field were studied during the maturation process, and a comparison with the bacteria inside rice seeds reported in a previous study was conducted. Culturable epiphytic bacteria were also isolated from the leaves and compared with the endophytic bacteria. The isolates were identified based on their 16S rRNA gene sequences. Many endophytes closely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
103
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 21 publications
12
103
0
Order By: Relevance
“…The type strain of A. ureilytica was originally reported as an isolate from air dust (Weon et al, 2007), but the closely related isolates (AB291857 and AB291900) have been identified on the surface and inside of rice leaves (Mano et al, 2007). The genus Aurantimonas has been recently established (Denner et al, 2003), and the biology of this genus in relation to the plant symbiosis is largely unknown, and needs to conduct further study.…”
Section: Discussionmentioning
confidence: 99%
“…The type strain of A. ureilytica was originally reported as an isolate from air dust (Weon et al, 2007), but the closely related isolates (AB291857 and AB291900) have been identified on the surface and inside of rice leaves (Mano et al, 2007). The genus Aurantimonas has been recently established (Denner et al, 2003), and the biology of this genus in relation to the plant symbiosis is largely unknown, and needs to conduct further study.…”
Section: Discussionmentioning
confidence: 99%
“…So far, a number of bacterial isolates from the rice phyllosphere have been characterized (Elbeltagy et al, 2000;Madhaiyan et al, 2007Madhaiyan et al, , 2009Mano et al, 2007) and potential beneficial interactions of phyllosphere bacteria with rice plants, such as plant growth promotion, for example, by bacterial nitrogen fixation or plant hormone production, and protection against pathogens have been studied (Madhaiyan et al, 2004;Maliti et al, 2005;De Costa et al, 2008;Yang et al, 2008;Chinnadurai et al, 2009;Pedraza et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…First, Microvirgula aerodenitrificans, the most abundant one, is an aerobic denitrifier [60] and has been reported previously as a rice endorhizosphere inhabitant [15]. Secondly Caulobacter sp., which has also been reported to be associated rice in two other parts of the world [61][62] [15] and to have PGP properties [48]. In the endorhizosphere of the DANAC SD20A rice cultivar, strains belonging to the Azospirillum, Acinetobacter and Citrobacter genera were dominant.…”
Section: Amplicon-based Taxonomic Profilingmentioning
confidence: 93%